2016
DOI: 10.1055/s-0042-115640
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment colonoscopy to diagnose serrated polyposis syndrome in a colorectal cancer screening population

Abstract: Background and study aims Serrated polyposis syndrome (SPS) is a high risk condition for colorectal cancer (CRC). Surveillance strategies for patients with serrated lesions remain controversial. We aimed to evaluate a diagnostic strategy to detect SPS consistently during reassessment colonoscopy in patients with proximal serrated lesions. Methods This was a retrospective study of all individuals from a fecal immunochemical test (FIT)-based CRC screening program (2010-2013) with one or more serrated lesions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…One of the most salient findings of our randomized controlled study is that after the scheduled follow-up colonoscopy, nine patients (22%) were reassessed as meeting SPS criteria, both the 2010's and the recently updated 2019's criteria, with important clinical implications in these patients. A similar finding was observed in a retrospective study of a fecal immunochemical test (FIT)-based CRC screening program [12], in which a 1year reassessment colonoscopy of arbitrary selected participants with previous serrated polyps detected by chromoendoscopy and high-definition endoscopes substantially improved SPS detection in those with proximal serrated lesions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…One of the most salient findings of our randomized controlled study is that after the scheduled follow-up colonoscopy, nine patients (22%) were reassessed as meeting SPS criteria, both the 2010's and the recently updated 2019's criteria, with important clinical implications in these patients. A similar finding was observed in a retrospective study of a fecal immunochemical test (FIT)-based CRC screening program [12], in which a 1year reassessment colonoscopy of arbitrary selected participants with previous serrated polyps detected by chromoendoscopy and high-definition endoscopes substantially improved SPS detection in those with proximal serrated lesions.…”
Section: Discussionsupporting
confidence: 75%
“…A randomized controlled trial in patients undergoing their first colonoscopy reported a non-significant trend toward detection of more proximal colon serrated lesions with NBI than with HD-WLE [11]. Finally, in a retrospective selected case series [12] of individuals in a population-based screening program with proximal serrated lesions at the baseline colonoscopy, colonoscopy reassessment within 1 year using chromoendoscopy and high-definition endoscopes led to a three-fold increase in the diagnosis of SPS.…”
Section: Introductionmentioning
confidence: 98%
“…In that sense, a recent study showed that in some patients with proximal serrated polyps, a strategy of reassessment colonoscopy using advanced endoscopy techniques can triple the total number of SPS diagnoses made in a fecal immunochemical testbased CRC screening program. 25 Therefore, it is possible that some of the MSP cases could develop SPS by fulfilling the WHO criteria in subsequent colonoscopies. Finally, the risk of CRC in MSP patients could be attributed in part to the higher number of adenomas these patients have.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 A recent Spanish FIT based cohort followed up all their patients with proximal serrated polyps, tripling the number of additional cases of SPS, for a final prevalence of 1:100. 50 Therefore, especially when using FIT in bowel cancer screening, colonoscopists should be alert to a diagnosis of SPS.…”
Section: Serrated Polyposis Syndrome Surveillancementioning
confidence: 99%